Comparative Analysis by Polymerase Chain Reaction Amplified Minicircles of Kinetoplast DNA of a Stable Strain of Trypanosoma cruzi from São Felipe, Bahia, its Clones and Subclones: Possibility of Predominance of a Principal Clone in this Area - Rozalia F Campos; Marilda S Gonçalves; Eliana AG dos Reis; Mitermayer G dos Reis; Sonia G Andrade (Memorias do Instituto Oswaldo Cruz, 1999)
Molecular characterization of one stable strain of Trypanosoma cruzi, the 21 SF, representative of the pattern of strains isolated from the endemic area of São Felipe, State of Bahia, Brazil, maintained for 15 years in laboratory by serial passages in mice and classified as biodeme Type II and zymodeme 2 has been investigated. The kinetoplast DNA (kDNA) of parental strain, 5 clones and 14 subclones were analyzed. Schizodeme was established by comparative study of the fragments obtained from digestion of the 330-bp fragments amplified by polymerase chain reaction (PCR) from the variable regions of the minicicles, and digested by restriction endonucleases Rsa I and Hinf I. Our results show a high percentual of similarity between the restriction fragment lenght polymorphism (RFLP) for the parental strain and its clones and among these individual clones and their subclones at a level of 80 to 100%.This homology indicates a predominance of the same "principal clone" in the 21SF strain and confirms the homogeneity previously observed at biological and isozymic analysis. These results suggest the possibility that the T. cruzi strains with similar biological and isoenzymic patterns, circulating in this endemic area, are representative of one dominant clone. The presence of "principal clones" could be responsible for a predominant tropism of the parasites for specific organs and tissues and this could contribute to the pattern of clinico-pathological manifestations of Chagas's disease in one geographical area.